Korelasi Pembelajaran Berdiferensiasi Dengan Keaktifan Dan Hasil Belajar Siswa Pada Mata Pelajaran PAI Di SDNdn 215 Bengkulu Utara - Pane, Mardiani; Eka Citra Dewi, Desy; Suradi, Ahmad (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2024)
The purpose of this study was to find out whether there is a correlation between differentiated learning and student learning outcomes at SDN 215 Bengkulu Utara. This study uses a type of quantitative research with an associative approach and data collected by ex post facto research. Hypothesis testing was carried out using the product moment correlation formula and concluded that differentiated learning with student learning activeness had a relationship of 0.495 with the level of closeness in the moderate/sufficient category. Through the t test it is known, t count > t table; 3.514 > 1.686, then the alternative hypothesis is accepted. Through the value of the coefficient of determination it is stated that differentiated learning affects the activeness of student by 24.5%. Test the hypothesis with the product moment correlation formula, differentiated learning with student learning outcomes has a relationship of 0.057 with the level of closeness of the relationship in the very weak category/ considered non-existent. Through the t test it is known that t count < t table; 0.3526 < 1.6860, then the null hypothesis is accepted. And through the coefficient of determination that the differentiation learning affects the student learning outcomes of 0.3262%.